The Impact of Interest Rate, Corruption Perception Index, and Economic Growth on Foreign Direct Investment in ASEAN-6 - Diella Rahmawati Fazira; Malik Cahyadin (Jurnal Keuangan dan Perbankan, 2018)
Foreign Direct Investment (FDI) becomes an economic indicator that drives economic development in developing countries. These countries need to identify some urgent indicators that attract FDI inflows. The interest rate policy is expected to become an effective instrument. This research analyzed the impact of economic growth, interest rate, and Corruption Perception Index (CPI) on FDI in ASEAN-6 in 2004-2016. ASEAN-6 were six of ASEAN member countries: Indonesia, Singapore, Malaysia, Thailand, Philippines, and Vietnam. The secondary data was collected from the reports of the World Bank, UNCTAD and Transparency International. This research used panel data with Fixed Effect Model (FEM). This research concluded that economic growth and interest rate had a positive and significant impact on FDI while CPI had a negative and significant impact on FDI. The recommendation of this research was the governments of ASEAN-6 maintain domestic economy to attract FDI. The domestic economy reflected by economic growth and interest rate. In addition, the governments need to improve the governance of FDI through the empowerment of anti-corruption institution.JEL Classification: E22, E43DOI: https://doi.org/10.26905/jkdp.v22i4.2355